COMPARATIVE ASSESSMENT OF ALOE VERA JUICE AND 0.06% CHLORHEXIDINE ON CANDIDA ALBICANS PLAQUE - Shanty Chairani; Sri W Rais; Rani Purba; Nabilah Nazalika (ODONTO : Dental Journal, 2019)
Background: Candida albicans is an opportunistic microorganism found in the oral cavity. High numbers of C. Albicans were often detected in dental plaque from children with caries. Aloe vera contains active compounds such as anthraquinone and flavanoid that have an antifungal effect against C. Albicans. The study aimed to compare the effect between Aloe vera juice and 0.06% chlorhexidine mouth rinse on C. Albicans colonies in plaqueMethod: Experimental study consisted of 30 children with carious teeth >4. Subjects were divided into two groups; Aloe vera juice and chlorhexidine 0,06%.Subjects were instructed to use 10 ml of each mouthwash twice daily for 7 days. At baseline and 7thdays, dental plaque samples were collected and then inoculated on saboroud dextrose agar. C. Albicans colonies were counted and expressed in CFU/ml.Result: The data were analyzed using a paired T-test and Mann-Whitney U test. A significant reduction on C. Albicans colonies in plaque was observed with Aloe vera juice (p<0,05), which was not significantly different from the control group (p>0,05).Conclusion: The present study suggested that Aloe vera juice can be used as amouthwash due to its ability in reducing C. Albicans in plaque.